The Effect of Knowledge of The Board of Budgets on Regional Financial Supervision With Public Policy Transparency as A Moderating Variable - Yohanis Rante; Aprianto La’lang Kuddy; Sarlota Arrang Ratang (Ridwan Institute, 2022)
The study aimed to examine the effect of the quality of board members' knowledge about budgets on regional financial oversight (APBD) with public policy transparency as a moderating variable that would strengthen or weaken those relationships. The analysis unit used in this study was a board member at the office of the Regional People's Representative Council (Assembly at provincial) of Papua Province, Jayapura regency Assembly at provincial, and Jayapura Assembly at provincial. Data collection is done using direct surveys, and then hypothesis testing is tested empirically using multiple regression analysis. This study shows that the board's knowledge variables about the budget affect regional financial supervision (APBD). In addition, the study could also prove that the interaction between public policy transparency and the board's knowledge of budgets does not affect APBD oversight The main purpose of this study was to examine the effect of the quality of the knowledge of the members of the council about the budget on the supervision of regional finances (APBD). Then this study adds the transparency variable as a variable that will moderate the relationship between the board's knowledge of the budget and APBD supervision, so it is hoped that it will strengthen or weaken the relationship. This study uses a quantitative approach with the method used is a survey research method. The unit of analysis used in this research is the council members at the Papua Province Regional House of Representatives (DPRD), Jayapura Regency DPRD, and Jayapura City DPRD. Data was collected by direct survey, then hypothesis testing was tested empirically using multiple regression analysis. The results of this study indicate that the board's knowledge of the budget variable has an effect on regional financial supervision (APBD). In addition, this study finds that the interaction between the variable of public policy transparency and the board's knowledge of the budget does not affect the supervision of the APBD